Influences of Edaravone on Necroptosis-Related Proteins and Oxidative Stress in Rats with Lower Extremity Ischemia/Reperfusion Injury: Influences of Edaravone on Ischemia/Reperfusion Injury - Zhao, Gang; Zhao, Li; Li, Yan; Wang, Lei; Hu, Zhipeng (Cellular and Molecular Biology, 2022)
The study aimed to investigate the influences of edaravone on necroptosis-related proteins and oxidative stress in rats with lower extremity ischemia/reperfusion (I/R) injury. The normal group (n=10), model group (lower extremity I/R injury model, n=10), treatment group (treatment with edaravone, n=10) and intervention group [lower extremity I/R injury model intervened with necrostatin-1 (Nec-1), n=10] were set. A conventional biochemical test was adopted to detect hepatic function indexes, and an enzyme-linked immunosorbent assay was performed to measure the levels of tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), malondialdehyde (MDA), superoxide dismutase (SOD) and myeloperoxidase (MPO). The apoptosis level in rat tissues was determined via terminal deoxynucleotidyltransferase-mediated dUTP nick end labeling (TUNEL) assay. The expression levels of genes and proteins were measured via quantitative polymerase chain reaction (qPCR) and Western blotting assay. The content of serum alkaline phosphatase (ALP), glutamic-pyruvic transaminase (GPT) and creatine kinase isoenzyme (CK-MB) was remarkably higher in the model group than that in the normal group. The levels of TNF-α, IL-6 and IL-1 were increased markedly in the model group, and the content of MDA in anterior tibial muscle tissues was also raised. The SOD content was elevated in the treatment group and intervention group. The number of apoptotic cells was larger than that in other groups (p<0.05). The gene expression levels of receptor-interacting protein kinase 1 (RIPK1), RIPK3, mixed lineage kinase domain-like (MLKL) and Caspase-3 were prominently higher in the model group than those in the treatment group and intervention group (p<0.05). The expression level of SOD in the treatment group and intervention group increased remarkably compared with that in the model group (p<0.05). RIPK1 and MLKL were raised evidently in the model group (p<0.05). Edaravone may regulate necroptosis-related proteins and oxidative stress in rats with lower extremity I/R injury by inhibiting the RIPK1-MLKL signaling pathway.